Evidence-based practice : an integrative approach to research, administration, and practice - Hall, Heather R.; Roussel, Linda (Burlington, MA : Jones & Bartlett Learning, 2022)
'This text is intended for graduate-level audiences in nursing research courses and is particularly well suited for those in administration tracks. It focuses on understanding how research-based evidence drives scholarly practice and how that evidence can justify innovation and policy change to improve patient outcomes. The new edition will add implementation and dissemination science applications to the EBP framework. It will feature health policy content and incorporate global and population health perspectives, content on informatics and technology, and educational strategies for patient and provider practices'--
Quantitative research -- Qualitative research -- Mixed methods research -- Data analysis -- Navigating the institutional review board -- Critical appraisal of research-based evidence.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 09, 2022).
WorldCat record variable field(s) change: 050
Keywords: Evidence-based medicine; Health services administration; Medicine -- Research -- Methodology; Evidence-Based Practice; Research Design; Health Planning -- organization & administration; Evidence-based medicine; Health services administration; Medicine -- Research -- Methodology; Electronic books; Electronic books